Designing meditation for doctor well-being: can 'Om' help obstetrics and gynaecology doctors?. (June 2020) - Allen, Rosie; Robinson, Andrew; Allen, Shelley; Nathan, Elizabeth; Coghlan, Edwina; Leung, Yee
Objective: The study aimed to measure the impact of meditation on participants' ability to regulate brain wave activity in high-stress situations, control physiological stress responses and improve subjective wellbeing. Methods: Twelve obstetrics and gynaecology (O&G) doctors meditated for 20 minutes daily for 21 days utilising a portable EEG (electroencephalogram) providing instantaneous audio feedback. Their brain activity levels and salivary cortisol were measured before and after performing three surgical procedures. Participants were interviewed about their experiences and completed self-ratings of distress (e.g. DASS-21, Depression, Anxiety and Depression Scale). Data were analysed statistically and thematically. Results: (a) Measures of pre- and post-operative brain activity showed no significantly higher levels of alpha waves. (b) Pre- and post-operative salivary cortisol levels did not significantly decrease. (c) DASS-21 scores showed significant decreases in levels of anxiety and stress. Conclusion: Results suggest that, with biofeedback meditation, O&G doctors can learn to reduce situational stress and improve mood overall through a focussed intervention.